An adaptive mesh refinement based flow simulation for free-surfaces in thermal inkjet technology. (June 2016) - Tan, Hua
Highlights: We propose an adaptive-mesh-refinement method to model thermal inkjet process. The vapor bubble is treated as an empty cavity with adiabatic gas expansion. A contact model is proposed and implemented on the embedded solid surfaces. The simulation code is verified and validated by a serial of examples. The proposed method can be widely applied in modeling of multiphase flows driven by thermal bubbles. Abstract: The microscopic multiphase flows of thermal inkjet (TIJ) devices usually involve a constantly changing liquid–gas interface. Often the curvature of the interface can become too high at some localized positions to be accurately resolved using a conventional static computational grid. A good solution to such challenging problem is to use the Adaptive-Mesh-Refinement (AMR) method, since AMR technique can concentrate the computational effort in the regions where it is needed most. In recent years, an open-source AMR code, Gerris, has been extensively used and benchmarked for a large variety of surface-tension dominated flows. However, the code cannot be directly used to model the TIJ process due to the lack of bubble dynamics and contact angle model for solid boundaries in the code. Therefore in the paper, we propose the following new approaches to model the TIJ flows and implement these algorithms in Gerris : (1) the vapor bubble is treated as an empty cavity so that its complex behavior of the vapor bubble after the bubble nucleation can be modeled using the adiabatic gas expansion and compression; (2) a height-function method based contact angle model is developed and implemented on the embedded solid surfaces. The new code has been verified and validated through a series of numerical examples and experimental tests. The proposed AMR method and the simulation code can be used in a broad range of applications in TIJ technology as well as multiphase flows of microfluidics.